Antimicrobial Susceptibility of Canadian Isolates of Helicobacter pylori in Northeastern Ontario. Issue 3 (2015) - Eng, Nelson F; Ybazeta, Gustavo; Chapman, Katrina; Fraleigh, Nya L; Letto, Rebecca; Altman, Eleonora; Diaz-Mitoma, Francisco
Abstract : BACKGROUND: Helicobacter pylori plays a significant role in gastritis and ulcers. It is a carcinogen as defined by the WHO, and infection can result in adenocarcinomas and mucosa-associated lymphoid tissue lymphomas. In Canada, rates of antimicrobial resistance are relatively unknown, with very few studies conducted in the past 15 years. OBJECTIVE: To examine rates of resistance in Sudbury, Ontario, compare antimicrobial susceptibility methods and attempt to determine the molecular basis of antibiotic resistance. METHODS: Patients attending scheduled visits at Health Sciences North (Sudbury, Ontario) provided gastric biopsy samples on a volunteer basis. In total, 20 H pylori isolates were collected, and antimicrobial susceptibility testing (on amoxicillin, tetracycline, metronidazole, ciprofloxacin, levofloxacin and clarithromycin) was conducted using disk diffusion and E-test methods. Subsequently, genomic DNA from these isolates was sequenced to detect mutations associated with antimicrobial resistance. RESULTS: Sixty-five percent of the isolates were found to be resistant to at least one of the listed antibiotics according to E-test. Three isolates were found to be resistant to ≥3 of the above-mentioned antibiotics. Notably, 25% of the isolates were found to be resistant to both metronidazole and clarithromycin, two antibiotics that are normally prescribed as part of first-line regimens in the treatment of H pylori infections in Canada and most of the world. Among the resistant strains, the sequences of 23S ribosomal RNA and gyrA, which are linked to clarithromycin and ciprofloxacin/levofloxacin resistance, respectively, revealed the presence of known point mutations associated with antimicrobial resistance. CONCLUSIONS: In general, resistance to metronidazole, ciprofloxacin/levofloxacin and clarithromycin has increased since the studies in the early 2000s. These results suggest that surveillance programs of H pylori antibiotic resistance may need to be revisited or improved to prevent antimicrobial therapy failure.